Paediatric knee anterolateral capsule does not contain a distinct ligament: analysis of histology, immunohistochemistry and gene expression. Issue 2 (3rd August 2020) - Iseki, Tomoya; Rothrauff, Benjamin B; Kihara, Shinsuke; Novaretti, João V; Shea, Kevin G; Tuan, Rocky S; Fu, Freddie H; Alexander, Peter G; Musahl, Volker
Abstract : Objectives: The presence of a discrete ligament within the knee anterolateral capsule (ALC) is controversial. Tendons and ligaments have typical collagens, ultrastructure, transcription factors and proteins. However, these characteristics have not been investigated in paediatric ALC. The purpose of this study was to characterise the paediatric ALC in terms of tissue ultrastructure and cellular expression of ligament markers scleraxis ( SCX )—a basic helix-loop-helix transcription factor—and the downstream transmembrane glycoprotein tenomodulin ( TNMD ), as compared with the paediatric lateral collateral ligament (LCL) and paediatric quadriceps tendon (QT). We hypothesised that, in comparison to the LCL and QT, the ALC would possess poor collagen orientation and reduced SCX and TNMD expression. Methods: 15 paediatric ALCs (age 6.3±3.3 years), 5 paediatric LCLs (age 3.4±1.3 years) and 5 paediatric QTs (age 2.0±1.2 years) from fresh cadaveric knees were used in this study. Fresh-frozen samples from each region were cryosectioned and then stained with H&E to evaluate collagen alignment and cell morphology. Expression of SCX and TNMD was determined by gene expression analysis and immunohistochemistry. Results: The histological sections of the paediatric LCL and QT showed well-organised, dense collagenous tissue fibres with elongated fibroblasts, while the ALC showed more random collagen orientation without clear cellular directionality. The aspect ratio of cells in the ALC was significantly lower than that of the LCL and QT (p<0.0001 and p<0.0001, respectively). The normalised distribution curve of the inclination angles of the nuclei in the ALC was more broadly distributed than that of the LCL or QT, indicating random cell alignment in the ALC. SCX immunostaining was apparent in the paediatric LCL within regions of aligned fibres, while the comparatively disorganised structure of the ALC was negative for SCX . The paediatric LCL also stained positive for TNMD, while the ALC was only sparsely positive for this tendon/ligament cell-surface molecule. Relative gene expression of SCX and TNMD were higher in the LCL and QT than in the ALC. Conclusion: In this study, a distinct ligament could not be discerned in the ALC based on histology, immunohistochemistry and gene expression analysis. Level of evidence: Controlled laboratory study.